Geoecologia das paisagens: fundamentos e aplicabilidades para o planejamento ambiental no baixo curso do Rio Curu-Ceará-Brasil - Vidal, Maria Rita (2014)
The thesis deals with the analysis of the dynamics of the landscape as a means for the environmental planning to use and occupate the APA (Environmental Protection Area) in the Estuary of Curu River and its surroundings, situated on the west coast of Ceará.The lack of environmental planning and the mismatch between the APA and ways of using this limited space led to the thesis to raise the proposal of redefinition of the APA limits so that it can encompass important environments for the functioning of landscapes. Making use of theoretical and methodological concepts of geoecology of landscapes, we have adopted the proposal of Rodriguez, Silva and Cavalcanti (2004), who emphasize on the structure and functioning of landscapes. As a result there is the existence of a landscape mosaic, with differences and specific characteristics in its geoecological structure. In determining the state, degradation and geoecological situation of the APA, the study showed that only 20% of goecological units are grouped in stable environmental state without any degradation and in favorable geoecological situation. The rest of the landscapes that make up the APA had shown unfavorable state and geoecological situation, which covers 80% of the studied landscapes, featuring unsatisfactory conditions to meet the environmental functions of those landscapes. The uses and occupations in the APA do not correspond with ground potential, and we have not observed forms of organization of using to ensure the optimization of the employment of the fundamental properties, structures and potential of landscapes.